Pelatihan Pembelajaran Bahasa Inggris untuk Anak Usia Dini pada Guru RA Se-Kabupaten Pasuruan - Ana Ahsana El-Sulukiyyah; Dewi Masitho Istiqomah; Rasyidah Nur Aisyah; Nur Hadi Gede Agustin (IKIP PGRI Bojonegoro, 2019)
This is a community service activity which was about English teaching and learning for young learners and its application in classes. The teachers of young learners needs to have knowledge about songs, games and media to teach English which is appropriate with learners’ and era’s need. Furthermore, this workshop is important to facilitate the teachers in giving the fun English materials. In this activitiy the teacher were trained to make the fun applicated media and the newest English nursery songs and games to be applied in their classes. It is hoped that this activity can facilitate the teachers in Kabupaten Pasuruan about the importantce of English learning for Young Learners, also teachers are hoped to be able to apply the fun and effective teaching learning process which is appropriate to the age and ability of the young learners and also appropriate with this era.Keywords: English teaching, teachers, workshop